The role of community and government digital culture in encouraging participation and the quality of public services in Bandung City - Imran, Ayub Ilfandy; Atnan, Nur; Ahmed, Ismail Sheikh Yusuf (International Journal of Communication and Society, 2023)
This research is motivated because the digital culture of the people of Bandung city is still low so that it has an impact on the low level of digital public participation and the digital culture of the Bandung city government is still low so that the quality of digital public services is also low. Therefore, this research was conducted to find out in more detail about how the digital culture of the community and its impact on the level of participation and how the digital culture of the Bandung city and its impact on the quality of public services in Bandung city and how strategies to build a digital culture so that public participation and the quality of public services in Bandung city become optimal. This research used a mix method, which is a combination of quantitative approaches and qualitative approaches. The quantitative approach in this study was carried out using a survey method to measure digital culture. While the qualitative approach was obtained through descriptive analysis of quantitative findings and constructing strategies to build a digital culture of the community and digital culture of the Bandung city government. The result of this research is that the digital culture of Bandung city is quite mature. However, it has not been able to encourage active and substantive participation in the government's digital communication channels. Likewise, the digital culture of Bandung city government employees is also quite good. The digital culture of government employees has only had an impact on service quality quantitatively, but not yet qualitatively.